Comprehensive Metabolomics Study in Children With Graves’ Disease - Xia, Qin; Qian, Weifeng; Chen, Linqi; Chen, Xiuli; Xie, Rongrong; Zhang, Dandan; Wu, Haiying; Sun, Hui; Wang, Fengyun; Liu, Jingjing; Chen, Ting (Frontiers in Endocrinology, 2021)
Abstract Objective. Graves’ disease (GD) related hyperthyroidism (HT) has profound effects on metabolic activity and metabolism of macromolecules affecting energy homeostasis. In this study, we aimed to get a comprehensive understanding of the metabolic changes and their clinical relevance in GD children. Methods. We investigated serum substances from 30 newly diagnosed GD children and 30 age- and gender-matched healthy controls. We explored the metabolomics using ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS) analysis, and then analyzed the metabolomic data via multivariate statistical analysis. Results. By untargeted metabolomic analysis, a total of 730 metabolites were identified in all participants, among which 48 differential metabolites between GD and control groups were filtered out, including amino acids, dipeptides, lipids, purines, etc. Among these metabolites, 33 were detected with higher levels, while 15 with lower levels in GD group compared to controls. Pathway analysis showed that HT had a significant impact on aminoacyl-transfer ribonucleic acid (tRNA) biosynthesis, several amino acids metabolism, purine metabolism, and pyrimidine metabolism. Conclusion. In this study, via untargeted metabolomics analysis, significant variations of serum metabolomic patterns were detected in GD children. Keywords: Graves’ disease; children; serum metabolomics; untargeted metabolomics；metabolic pathway